PECULIARITIES OF THE FORMATION OF YIELD AND INDIVIDUAL QUALITY CHARACTERISTICS OF WINTER WHEAT GRAIN DEPENDING ON THE SOWING DATES (INNOVATIVE ECONOMY, 2026)
Yashchuk T.S., Samets N.P., Dovhan O.M., Kuzyshyn N.S. PECULIARITIES OF THE FORMATION OF YIELD AND INDIVIDUAL QUALITY CHARACTERISTICS OF WINTER WHEAT GRAIN DEPENDING ON THE SOWING DATESPurpose. The aim of the article is to investigate the peculiarities of the formation of winter wheat grain yield and quality depending on the sowing dates in the conditions of the Western Forest-Steppe of Ukraine and to conduct an economic assessment of the technology of its cultivation.Methodology of research. The theoretical and methodological basis of the research was specialized and generally accepted methods and techniques used in agronomy. General scientific and special methods were used to achieve the set goal, namely: induction and deduction – for searching, systematizing and processing the information under study; logical – for generalizing the processed data set; field – for observing the growth and development of plants during the growing season, the formation of yield; laboratory – for determining the qualitative indicators of grain; mathematical and statistical – conducting variance analysis; computational and comparative – for determining yield, economic assessment of the studied elements of technology; tabular and graphical – for a visual presentation of systematized information; abstract and logical and generalization – for forming conclusions and proposals from the research.Findings. The ecological and economic rationality and efficiency of using new varieties of domestic selection for sowing them at optimal times have been substantiated. Effective technological elements for increasing the yield and quality of grain have been developed and the features of the formation of productivity of winter wheat varieties depending on the sowing dates in conditions of climate change have been determined. An economic assessment of the effectiveness of the recommended elements of the winter wheat growing technology has been calculated.It has been established that a clear trend towards increasing the productivity of winter wheat at later (october) sowing dates is becoming more noticeable (+0.92 t/ha and +1.39 t/ha). In the last two years, the shift of the optimal sowing dates of winter wheat to an even later period has been observed, namely from October 5 and onwards.High productivity indicators of winter wheat plants are formed during sowing in the period from 5.10 to 25.10, which ensured the highest yield of high-quality grain: 8.64–9.21 t/ha, conditional net profit – 38468–42438 UAH/ha, profitability level – 187.8–206.2%. A trend of growth in quality indicators in grain during sowing in late terms was noted.The introduction of effective technological elements of managing the productivity of grain eared crops in the conditions of the Western Forest-Steppe will contribute to the growth of high-quality grain production and economic feasibility, which is ensured by the return on invested funds.Originality. Substantiation of the peculiarities of yield formation, qualitative characteristics of winter wheat grain at different sowing dates and determination of the economic efficiency of its cultivation technology in specific soil and climatic conditions of the Western Forest-Steppe zone has been further developed.Practical value. Technological methods for growing winter wheat have been improved, which will ensure the formation of highly productive agrocenoses with a high level of profitability. The results of scientific research can be used to implement effective technological elements for managing the productivity of grain crops in the conditions of the Western Forest-Steppe.Key words: grain crops, yield, grain quality, competitiveness, profitability.
Keywords: grain crops; yield; grain quality; competitiveness; profitability